2010
DOI: 10.19030/jabr.v26i5.319
|View full text |Cite
|
Sign up to set email alerts
|

Determinants Of Integrated Performance Measurement Systems Usage: An Empirical Study

Abstract: <p class="MsoNormal" style="text-align: justify; margin: 0in 0.5in 0pt; mso-pagination: none;"><span style="color: black; font-size: 10pt; mso-bidi-font-weight: bold; mso-ansi-language: EN-GB; mso-themecolor: text1;" lang="EN-GB"><span style="font-family: Times New Roman;">Performance management literature has been advocating the balanced use of non-financial measures alongside traditional financial measures, possibly within integrated performance measurement systems, since the early 1990&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
8

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 8 publications
0
7
0
8
Order By: Relevance
“…L'utilisation de diverses techniques n'est pas uniforme, les recherches confirment l'influence des facteurs contingents traditionnels : la taille de l'entreprise (Szychta, 2002;Marc et al, 2010b;Cadez et Guilding, 2008;Siska, 2015), la stratégie de l'entreprise (Rejc, 2004;Tekavčič et al, 2005;Cadez et Guilding, 2008;Peljhan et Tekavčič, 2008), l'environnement (Čadež et al, 2005;Marc et al, 2010b), la technologie (Rejc, 2004). De plus, plusieurs travaux montrent également que d'autres facteurs influencent les techniques et les outils de contrôle, notamment : le contexte culturel (Mayr, 2012), les connaissances de l'entreprise sur les outils de gestion (Marc et al, 2010b), le pouvoir des syndicats (Rejc, 2004;Rejc et Slapnicar, 2004), la forme juridique (Rejc et Slapnicar, 2004). L'incidence de l'usage des systèmes de contrôle de gestion sur les performances financières suscite l'intérêt des chercheurs, mais reste un sujet controversé.…”
Section: Figureunclassified
“…L'utilisation de diverses techniques n'est pas uniforme, les recherches confirment l'influence des facteurs contingents traditionnels : la taille de l'entreprise (Szychta, 2002;Marc et al, 2010b;Cadez et Guilding, 2008;Siska, 2015), la stratégie de l'entreprise (Rejc, 2004;Tekavčič et al, 2005;Cadez et Guilding, 2008;Peljhan et Tekavčič, 2008), l'environnement (Čadež et al, 2005;Marc et al, 2010b), la technologie (Rejc, 2004). De plus, plusieurs travaux montrent également que d'autres facteurs influencent les techniques et les outils de contrôle, notamment : le contexte culturel (Mayr, 2012), les connaissances de l'entreprise sur les outils de gestion (Marc et al, 2010b), le pouvoir des syndicats (Rejc, 2004;Rejc et Slapnicar, 2004), la forme juridique (Rejc et Slapnicar, 2004). L'incidence de l'usage des systèmes de contrôle de gestion sur les performances financières suscite l'intérêt des chercheurs, mais reste un sujet controversé.…”
Section: Figureunclassified
“…Fonte: Beuren, Santos e Hein (2015). Gradvohl e Fleck (2015), ao realizarem a revisão da literatura, abordam que a maior parte dos estudos sobre o tema não explicita as diferenças sobre os conceitos e que as principais definições citadas, de Cyert e March (1963), de Bourgeois (1981) e de Nohria e Gulati (1997), apresentam diferentes contextos, estados, fontes, funções, resultados e tipos de folga. Para Gradvohl e Fleck (2015), após detalharem essas três principais definições, a .]…”
Section: Tan E Peng (2003)unclassified
“…Ao analisarem se a folga organizacional financeira possui relação com as empresas que adotaram BSC, Marc et al (2010) constataram que as firmas atuantes em mercados regulados tendem a utilizar mais do BSC, frente aos outros setores analisados, tendo em vista a pressão dos agentes reguladores pela evidenciação de informações não financeiras em seus relatórios e por sofrerem menores pressões competitivas para investirem no BSC. Dietshi e Nascimento (2007) constataram que o BSC possui mais aderência às empresas abertas do que às fechadas, apontando os aspectos financeiros como mais relevantes para essa divergência.…”
unclassified
See 1 more Smart Citation
“…Vámosi (2000), using a case study, found the environment an important contingent factor of the development of accounting and reporting practice. Marc et al (2010b) explored how contextual factors (company size, industry, or market position), business objectives, and knowledge about contemporary management tools influence the decision to implement the Balanced Scorecard or similar integrated PMS. Company size, industry, and management knowledge have been confirmed as contingencies.…”
Section: Multidimensionalitymentioning
confidence: 99%